Pengembangan Permainan Pecah Piring Sintren: Pemanfaatan Olahraga Tradisional pada Pembelajaran untuk Meningkatkan Kemampuan Motorik Kasar Anak - Kamaludin, Kamaludin; Ngadiman, Ngadiman; Festiawan, Rifqi; Kusuma, Indra Jati; Febriani, Ayu Rizky (Prodi PGSD Penjas FPOK UPI, 2020)
Currently traditional games are rarely played by children along with the times, even though several studies mention that traditional games have a very important role in stimulating the gross motor development that is owned by every child. This research aims to create new game products from traditional sport modifications that are appropriate to be used and can potentially develop the gross motor skills of children aged 9-12 years. The research method used is Research and Development (RD) which is carried out by the steps of: 1) Product Design, 2) Validation Phase 1, 3) Design Revision, 4) Second Stage Validation, 5) Trial of Small Scale Products, 6) Product Revision, 7) Final Product. The research sample was 30 students at Widarapayung Wetan State Elementary School 02 grades IV, V, VI. The research instrument was in the form of a questionnaire containing statements validated by experts, then the scores obtained were processed and converted into product evaluation criteria. The results of this study obtained an assessment of game experts by 94% or the category of